Circularly polarized photoluminescence and Hanle effect measurements of spin relaxation in organic–inorganic hybrid perovskite films. Issue 12 (7th March 2018) - Wang, Ruizhi; Hu, Shu; Yang, Xiao; Yan, Xiaoliang; Li, Heng; Sheng, ChuanXiang
Abstract : Partial circularly polarized photoluminescence with polarization degree of 2% from CH3 NH3 PbBr3 film at 77 K is observed, excited using a circularly polarized 532 nm laser. Moreover, the Hanle effect is measured to study spin relaxation in CH3 NH3 PbBr3 film, yielding a spin lifetime of ∼240 ps at 77 K. Abstract : Partial circularly polarized photoluminescence (CPL) with a polarization degree ( P ) of 2% from CH3 NH3 PbBr3 film at 77 K is observed, excited by a circularly polarized 532 nm laser. However, P decreases to 0.3% when excited using a circularly polarized 447 nm laser, and to zero using a linear polarized laser. The Hanle effect is measured to study spin relaxation in CH3 NH3 PbBr3 film, yielding a spin lifetime of ∼240 ps at 77 K, which however becomes one order of magnitude smaller when the temperature increases to 110 K. The existence of a CPL that is dependent on the helicity of the excitation laser, and the unexpectedly long spin lifetime with large spin–orbit coupling, suggest the potential of hybrid perovskites for spintronic applications.